A Twice-born God. Reimagining the Myth in Euripides’ Bacchae - Пилиповић, Јелена (Bulletin of the Institute of Ethnography SASA, 2023)
The paper examines the myth of Dionysusʼs double birth as a hidden semantic axis of the Bacchae, starting from the hypothesis that the importance of this narrative goes beyond the poetic context in which it is found and that it represents an important step in the reimagining of the concept of myth, which occurs at the height of the polis culture. Having come to Thebes to prove his divine nature and Zeus’ paternity, Dionysus, in the incipit, before saying his name, defines himself as “the child of Zeus”, while in the final epiphany he defines himself as “divine offspring”. Neither the divine nature of Dionysus, nor the fatherhood of Zeus in the tragedy are proven explicitly, but only implicitly – through the ability of the young god to dissect the human mind, reason, rational will, thus confirming and strengthening the sphere of the irrational, to which the myth remains firmly attached. The paper aims at proving the hypothesis that this attachment of the myth to the sphere of the non-rational is the Euripides’ decisive contribution to the transformation of the concept of myth.
Keywords: myth; divine nature; epiphany; Dionysus; Euripides